Boonniyom Market’s Model in Thai Socciety - Soungbunlue , Plernpit; Chanraeng, Thepprawin; Kotsupho, Prisit; Vichai, Virot; Klajon, Jaiphet (Journal of Dhamma for Life, 2026)
This article aims to examine the concept of Boonniyom within the Asoke community, analyze the Boonniyom market under the Thai social context, and propose a Boonniyom market model applicable to contemporary society. The study is grounded in the problem of moral decline in mainstream market-based economic systems, which has led to issues of product quality, unfair pricing, and social inequality. It seeks to explore a value-based alternative that does not prioritize profit maximization as its central objective. This research employs a qualitative methodology, combining documentary research with fieldwork. Data were collected through in-depth interviews, focus group discussions, and participant observation. Key informants were purposively selected from Asoke communities across the four regions of Thailand, totaling 23 participants. These informants included community coordinators, producers, sellers, consumers, Asoke monastics, and scholars of Buddhism. The data were analyzed using content analysis. Findings reveal that Boonniyom is a concept aimed at reducing individual selfishness through economic practices. It effectively addresses the problem of high production costs, which is a major weakness and constraint of many alternative markets. As a result, the Boonniyom market is able to produce and distribute good-quality products at low and fair prices, grounded in honesty, generosity, and mutual support. The Boonniyom market model in Thai society consists of five key components: (1) the Four Virtuous Commerce Principles—morally acceptable products, fair pricing, virtuous buyers and sellers, and places conducive to generosity; (2) value-oriented objectives; (3) operational processes; (4) evaluation mechanisms; and (5) conditions for success, including low production costs, collective production among virtuous networks, and the outcomes of merit and karma. This model reflects the potential of the Boonniyom market as an ethical alternative market within contemporary Thai society.